국내 주요 정수장의 과불화화합물 분포 및 위해성 평가 - 손보영; 이이내; 양미희; 박상민; 표희수; 이원석; 박주현 (대한상하수도학회, 2017)
The chemical structures of perfluorinated compounds(PFCs) have unique properties such as thermal and chemical stability that make them useful components in a wide variety of consumer and industrial products. Two of these PFCs, perfluorooctane sulfonate(PFOS) and perfluorooctanoic acid(PFOA), have received attention and were the most commonly detected. In this study it was analyzed the concentrations of 8 PFCs in samples were collected from drinking water treatment plants for 5 years(2012-2016). PFOS and PFOA were also high concentration and frequency. The mean concentrations of PFOA and PFOS were detected 0.0026-0.0069 μg/L and 0.0009-0.0024 μg/L in samples from drinking water treatment plants. These were relatively lower or similar compared to PFOS concentrations in Osaka(Japan). In general, these levels are below health-based values set by international authoritative bodies for drinking water. These results will be serve as the first monitoring data for PFCs in drinking water and be useful for characterizing the concentration distribution and management of PFCs in future studies.